Contribution of Environmental Factors and Infectious Diseases Towards Infant Mortality in Rembang District - Pawenang, Eram Tunggul; Nikmah, Siti Lailatun (Unnes Journal of Public Health, 2022)
Statistics indicate that the Infant Mortality Rate (IMR) is in the ratio of 17.7/1000 live births in Rembang District, Central Java Province. Therefore, this study sought to determine the contribution of infectious diseases and environmental factors to high infant mortalities recorded in this region. The study implemented an observational analysis with a case-control design with 64 respondents, consisting of equal case and control samples. The sample was selected through purposive sampling, while data collection involved interviews and observations methods. From the results, the variables strongly related to the incidence of infant mortality were ventilate condition with an OR = 5,672 and 95% CI = 1.525 – 21.104 and infectious diseases with an OR = 4.211 and 95% CI = 1.313 – 13.508. Also, the infectious diseases and condition of ventilate variables signified an interaction with a p-value = 0.001.